The study of hyperphagia in dementia - Keene, J; Keene, Janet (1995)
About 750 000 people suffer from dementia in the United Kingdom. This number is rising as the proportion of those over 65 years old increases. Excessive eating (hyperphagia) occurs at some stage in about 25 % of people suffering from dementia. This can lead to consumption of unsuitable substances and a significant gain in weight, which may make care at home impossible. Until now, reports of hyperphagia have been purely anecdotal. The aims of this thesis were to develop objective methods for the definition and measurement of hyperphagia and to use these as a basis for examining the phenomenon of hyperphagia in detail. Two standardised and reliable methods for quantifying hyperphagia were developed and compared. Results showed that people with hyperphagia ate, on average, more than three times the quantity of food eaten by matched controls during test meals. The hyperphagic group were compared, in a series of experiments, with two control groups - subjects with dementia who were not hyperphagic and normal elderly. The food choice of the hyperphagic group differed significantly from normal elderly: they chose less protein and low-energy foods and ate more sweet food. The changes in food choice seem to be a more severe form of the changes which occur during the dementing process. Examining the microstructure of eating showed that the mechanisms controlling both the onset and cessation of feeding are abnormal. Satiety was examined by giving subjects and controls two preload drinks of different energy content and examining the effect on subsequent food intake. Compensation for the preload was found to be weaker in normal elderly controls and both dementia groups when compared with young controls. Although people with hyperphagia show significantly more patterns of stereotyped behaviour than matched demented controls the prolonged period of eating does not seem to be due to a stereotypy but to a delay in the satiation mechanism. Hyperphagia typically occurs in the middle stages of the dementing illness and lasts for a mean of about three years. These studies demonstrated that subjects with dementia who are hyperphagic have a major disturbance in the mechanisms controlling satiation, hunger, food choice and satiety.